Analisis Penerapan Keselamatan dan Kesehatan Kerja (K3) pada Kegiatan Bongkar Muat CBU Menggunakan Ramp Door di Pelabuhan - Mahendra Galih Prasaja; Himawan Aditya Pratama; Vivid Dekanawati; Sumardi Sumardi; Ayu Rizka Anggraini; Ahmad Sabiq; Ferry Hamdani; Amella Juanicha (Politeknik bumi Akpelni, 2026)
Loading and unloading activities of Car Built Unit (CBU) cargo at ports involve a high risk of occupational accidents due to the interaction between workers, vehicles, and loading facilities. One of the most critical facilities is the ramp door, which serves as the main access for vehicles entering and leaving Roll-on/Roll-off (Ro-Ro) vessels. This study aims to analyze the implementation of Occupational Safety and Health (OSH) practices and identify the dominant risks associated with ramp door operations during CBU loading and unloading activities at Tanjung Priok Port. A quantitative approach was employed through field observations using an OSH assessment instrument covering personnel, equipment, operational procedures, work environment, and management supervision. Risk analysis was conducted using the Failure Mode and Effect Analysis (FMEA) method by evaluating Severity, Occurrence, and Detection to determine the Risk Priority Number (RPN). The findings indicate that the implementation of OSH achieved a score of 75%, categorized as good. FMEA identified slippery ramp door surfaces as the highest-priority risk, with an RPN value of 48. Therefore, regular inspections, anti-slip surface improvements, enhanced lighting, and stricter compliance with operational procedures are recommended to improve occupational safety and the operational performance of CBU loading and unloading activities.